Wpływ zmian wielkości rodziny oraz jej dochodów na wielkość konsumpcji żywności i prace wykonywane w gospodarstwie domowym - Newton Morgan, James (Wydział Prawa i Administracji UAM, 1985)
In the article the author has presented the research focused on the impact of changes in family composition, size and in income on food consumption and housework in the U.S.A. in the years 1975 and 1979. The author has used interviews made in 1975, 1976, 1979 and 1980. At the beginning of the article the author has presented previous work in that field. The article presents a dynamic model based on the effects of income and its components, and of family size and composition, and of wife's paid work as exogenous variables on food consumption and housework hours. Features of a complete dynamic model, where food consumption and housework were treated as endogenous, have also been discussed. The empirical analysis has been put in a dynamic form, reducing the need to account for stable interpersonal differences. The author ha;s started with a static equilibrium model. Then the differences between 1979 and 1975 have been worked out to derive a model of changes. It has been assumed that the effects of income (values of variables have been expressed in 1979 dollars) and family members wer stable across time, and also that personal attributes or environment did not change and hence did not effect changes in food consumption. The main findings of the research have been presented in the final part of the article. Changes in the numbers of family members of different age-sex combinations have the expected effects on food consumption, correlated with well known calorieprotein requirements. Changes in family composition do effect changes in the wife's paid work hours, and those changes have in turn assymetrical effect on family food consumption. Both increases and decreases in the wife's work hours increase family food consumption. They increase it more for total food, but significantly even for food consumed at home. Changes in taxable money income have small but significant effects on food consumption, and on the fraction of it spent eating out, i.e., more effects on eating out. Transfer income from AFDC have a much larger effect on food consumption, mainly on food consumed at home. Work — related transfers have only a marginal effect increasing food consumption, but a significant effect increasing the fraction spent eating out. Inreases in imputed rent are associated with significant increases in total food but not in home food consumption or in the fraction spent eating out. Increased food stamp bonus significantly decreases the fraction spent eating out — the effect is almost entirely on home consumed food. Decreases in the food stamp bonus have much larger effects on food consumption than increases. All but one the changes in family — members types has a significant effect on housework, and they are reasonable and consistent with other estimates. Income changes have no significant effects on housework, except for changes in work — related transfers, which makes sense since unemployment or disability means more work around the house. Finally, in the line with other studies of the double time — burden on working wives, changes in the wife's paid work hours have no significant effect on housework hours.
Effects of changing family composition and income on food consumption and housework